Curva de retenção de água em substrato de fibra de coco para cultivo em vasos em ambiente protegido - Nascimento, Erlen kaline Ávila do (Universidade Federal Rural do Semi-Árido, 2018)
The crop production in substrate in protected environment requires irrigation to be managed according to the water content in the area with the highest root activity. Irrigation monitoring is a way of verifying the effectiveness of irrigation and can be done using tensiometers, which measure the tension with which water is retained in substrates such as coconut fiber. To allow irrigation management, it is important to determine the water retention curve of coconut fiber. In this sense, the objective of this work was to determine the retention curve of coconut fiber Golden Mix for cultures on substrates, using the tensiometer method. The work was carried out in a protected environment at the Federal Rural University of the Semi-Arid, in MossoróRN, Brazil. The procedure adopted was to determine the water tension in the Golden Mix coconut fiber substrate and the immediate weighing of the pots to determine the corresponding amount of water by difference. The tensions were obtained through tensiometers equipped with pressure transducers and the readings were performed in a data acquisition system, the weighing was carried out by means of an electronic scale with a capacity of 20 kg. Pressure, water amount and substrate density data were used for the preparation of the water retention curves by the substrate. The results indicate the possibility of the use of tensiometers to determine the water retention curves in the coconut fiber substrate. The water content of the coconut fiber is up to 2.30 g g-1 of water, or up to 0.35 cm3 cm-3 in volumetric base.
Monografia
Keywords: Tensiômetro; Substrato agrícola; Manejo da irrigação; Tensiometer; Agricultural substrate; Irrigation management; CIENCIAS AGRARIAS::AGRONOMIA